1990
DOI: 10.1200/jco.1990.8.8.1408
|View full text |Cite
|
Sign up to set email alerts
|

Phase II trial of Serratia marcescens extract in recurrent malignant astrocytoma.

Abstract: Nineteen assessable patients with recurrent malignant astrocytomas who had failed standard therapy (surgery, radiation, and/or chemotherapy) were treated on a phase I-II trial with a biologic extract of Serratia marcescens (ImuVert; Cell Technology, Boulder, CO) a new biologic response modifier (BRM). Two complete responses (CRs) were seen, of 63 and 77+ weeks duration. One minor response (MR) occurred, of 6 weeks duration. There were four additional stable (S) patients, with durations of 58+, 39, 12, and 7 we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1993
1993
2004
2004

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…Passive immunotherapy with monoclonal antibodies has had its best success via intrathecal injection for meningeal tumor 28 . Restorative or nonspecific immunotherapy has been shown to have beneficial effects on tumor shrinkage (β‐interferon, 29 γ‐interferon, 30 and Imuvert 31 ). Combinations of these therapies with radiation and chemotherapy and with each other are being studied and are likely to be routes for the future.…”
Section: Hemispheric Gliomasmentioning
confidence: 99%
“…Passive immunotherapy with monoclonal antibodies has had its best success via intrathecal injection for meningeal tumor 28 . Restorative or nonspecific immunotherapy has been shown to have beneficial effects on tumor shrinkage (β‐interferon, 29 γ‐interferon, 30 and Imuvert 31 ). Combinations of these therapies with radiation and chemotherapy and with each other are being studied and are likely to be routes for the future.…”
Section: Hemispheric Gliomasmentioning
confidence: 99%
“…Furthermore, these early trials suggested that ImuVert has activity in several tumor types including prostate cancer [3,4]. Phase II studies have begun in several tumor types and preliminary results have demonstrated activity in gliomas [6]. For these reasons we initiated a Phase II trial in patients with metastatic prostatic cancer.…”
Section: Discussionmentioning
confidence: 99%
“…54 One clinical trial performed in patients with recurrent malignant gliomas revealed a response rate of 16%. 55 In another study of ImuVert and concurrent radiation therapy, some toxicity in the form of hypotension was encountered, with survival similar to that of standard therapy in historical controls. 56 Along similar lines, immunization with a killed tumor cell vaccine modified with Newcastle disease virus has been reported to have an effect on tumors.…”
Section: Clinical Immunotherapy Trials For Gliomamentioning
confidence: 94%